ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI KABUPATEN KARANGASEM PROVINSI BALI - Pemayun, Dewa Gede Dalem Vedanta Sastra; Arka, Sudarsana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023DO - 10.24843/EEB.2023.v12.i12.p10, 2023)
This study aims to determine the factors that influence the level of poverty in Karangasem Regency, Bali Province. The source of data in this study is secondary data using time series data. The amount of time series data is 15 years for each variable starting from 2006 to 2020. The analytical technique used in this study is multiple linear regression analysis model. The results of the study stated that 1) The level of education, unemployment and population had a significant effect on the poverty level in Karangasem Regency, Bali Province, 2) Partially showed that the education level partially had a negative and significant effect on the poverty level in Karangasem Regency, Bali Province, partial unemployment. has a positive and significant effect on the poverty level in Karangasem Regency, Bali Province, and the population has no significant effect on the poverty level in Karangasem Regency, Bali Province.